Instrumental conditioning of diastolic blood pressure in essential hypertensive patients - Elder, S. Thomas (1973)
Eighteen male essential hypertensive patients participated in an experiment designed to compare two strategies for controlling high blood pressure. Each strategy was derived from the instrumental learning literature, and the aim was to treat the blood pressure response as an operant and determine the most effective conditioning procedure for manipulating it. The results demonstrate that patients could be conditioned to lower blood pressure by 20% to 30% over a period as brief as four days by providing an external signal and verbal praise contingent upon each reduction in diastolic pressure that met a pre-set criterion.